Analkarzinom: Zusammenspiel ambulanter und stationärer Patientenversorgung : Leitthema - Fritz, Stefan; Ruder, Arne Mathias; Bussen, Dieter G.; Reißfelder, Christoph; Hardt, Julia (Die Chirurgie, 2025)
Background Anal cancer is a rare but increasingly more frequently diagnosed entity. The treatment mostly consists of a combination of surgery and/or combined radiotherapy/chemotherapy. In advanced cases, extensive visceral resection may be necessary. In most cases, treatment is interdisciplinary and includes both outpatient and inpatient treatment phases. Objective The aim of this work is to shed light on the most important steps in the diagnostics and treatment of anal cancer with a focus on the interaction between outpatient and inpatient patient care. Material and methods To determine the evidence base for this article, a literature search was conducted in the PubMed database. In addition, the current guidelines and recommendations were included. Results Outpatient facilities are often responsible for initial diagnostics and follow-up care, while inpatient facilities are responsible for implementing the complex treatment measures. This interaction presents challenges, particularly in coordinating treatment processes, communicating relevant information and adhering to time schedules. Delays in the referral or follow-up care can lead to a worsening of the prognosis. Conclusion Multimodal and interdisciplinary treatment is essential for the successful treatment of anal cancer. Cross-sectoral cooperation between outpatient and inpatient care plays a central role. This is the only way to ensure the best possible oncological treatment while maintaining the quality of life.
Online publiziert: 27. Juni 2025
Gesehen am 25.09.2025